Composition of Shrimp Species Associated with Mangroves in the Lembar Coast of West Lombok - Abdul Syukur; Sajili, Lalu Alvin Maulana; Al Idrus, Agil (Jurnal Biologi Tropis, 2024)
Mangroves are a type of plant that grows in coastal areas and river estuaries, and are often exposed to sea tides. The mangrove ecosystem has an important role for the life of the biota along the ecosystem, such as shrimp. Therefore, the aim of this research is to assess the composition of shrimp associated with mangroves in the Lembar coast of West Lombok. Mangrove data were collected using transect and quadrant methods, while shrimp data was collected using seser nets. Next, data analysis was carried out descriptively and the relationship between shrimp density and mangrove density was analyzed using Pearson correlation. The results of the research found four species of shrimp, including Penaeus merguiensis, Penaeus monodon, Alpheus sp, and Litopenaeus vannamei. Apart from that, six mangrove species were found, including Avicennia alba, Avicennia marina, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa and Sonneratia alba. Furthermore, the shrimp density value on the Sheet coast is 1756 ind/ha/year, while the mangrove density value is 0.382 ind/m2. The relationship between shrimp and mangroves is based on Pearson correlation analysis, r2 value = 0.699. The conclusion of this research is that the level of correlation between shrimp density and mangrove density in the Lembar coast is in the medium category.